Toward Win-Win Regionalism in Asia: Issues and Challenges in Forming Efficient Trade Agreements - Michael G. Plummer (Asian Development Bank (ADB), 2006)
Many economists tend to be skeptical of the merits of Free-Trade Areas (FTAs) due to their second-best nature, while others support them under certain conditions, particularly as they allow for a more comprehensive treatment of trade- and investment-related issues than is currently possible under the 149-member WTO. This paper endeavors to bridge this analytical chasm by developing a blueprint for "first-best" regionalism based on "best practices". It then applies the associated set of rules to existing FTAs in Asia (both intra- and extra-regional) to guage the degree to which they approach best practices. In summary, we find that most accords receive high marks in most areas, with the exception of "rules of origin" and certain service sectors.
hdl:11540/1884
Keywords: F15; 330; Asian integration; free trade agreement; best practices; Asian development